Current challenges in cell wall biology in the cereals and grasses - Burton, Rachel; Fincher, Geoff (Frontiers in Plant Science, 2012)
There has been a recent surge of interest in plant cell wall biology, based on the recognition that cell walls are key contributors to dietary fibre, which in turn has been shown to bring significant benefits in human health and nutrition, together with the importance of cell walls as major constituents of lignocellulosic residues that are being developed as renewable sources of biofuels. In both applications, the cell walls of the Poaceae, which include the commercially cereals and grass species. The cell walls of the grasses differ in composition to most other vascular plants, insofar as they contain cellulose and relatively high levels of heteroxylans as ‘core’ polysaccharide constituents, in addition to lignin in secondary cell walls and smaller amounts of heteromannans, pectic polysaccharides and xyloglucans. In certain cells of the grasses and cereals walls also contain (1,3;1,4)-β-glucans, which are not widely distributed outside the Poaceae. Although the genes involved in cellulose and (1,3;1,4)-β-glucan synthesis have been identified, mechanisms that control expression of the genes are not well defined, and there are central aspects of the cell biology and biochemistry of wall synthesis that are not completely understood. In the case of the heteroxylans, genes that mediate their biosynthesis have been identified, but again we do not have a complete understanding of the biosynthetic process.